Youth crime, public policy, and practice in the juvenile justice system: recent trends and needed reforms - Jenson, Jeffrey M.; Howard, Matthew O. (1998)
Historically, juvenile justice policy has oscillated between rehabilitative and punitive approaches to managing young offenders. Policy and practice in the 1970s and 1980s emphasized individual treatment for young offenders in nonsecure, community-based programs. An increase in violent youth crime during the past decade has renewed interest in punishing delinquent youths. Cyclic fluctuations in juvenile justice policy and their relationship to policy, practice, and youth crime are examined. Our analysis suggests that overall crime rates have remained relatively stable over the past three decades and are independent of prevailing juvenile justice policies. The findings support the need for targeted prevention efforts addressing the root causes of juvenile crime. Needed policy reforms, public education efforts, and practice approaches are outlined. - Reproduced
Keywords: Justice; Social problems; Social policy; Crime; Youth; Juvenile delinquency